Mormonism : a very short introduction - Bushman, Richard L. (Very short introductions, 2008)
Beginning with a handful of members in 1830, the church that Joseph Smith founded has grown into a world-wide organization with over 12 million adherents, playing prominent roles in politics, sports, entertainment, and business. Yet they are an oddity. They are considered wholesome, conservative, and friendly on one hand, and clannish, weird, and self-righteous on the other. Mormonism: A Very Short Introduction explains who Mormons are: what they believe and how they live their lives. Written by Richard Lyman Bushman, an eminent historian and practicing Mormon, this compact, informative volume.